PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL AMARIS TENDEAN JAKARTA - Hafizh fadhlil; Yhonanda Harsono (Journal of Research and Publication Innovation, 2025)
This reasearch aims to determine the influence of motivation and work discipline on employee performance partially and simultaneously at the Amaris Tendean Hotel Jakarta. This research method uses a quantitative analysis method, namely using 60 respondents. Data analysis techniques in this research are using instrument test, validity tests, reliability tests, normality tests, multicolinearity tests, heteroscedasticity tests, multiple linear regressionanalysis, multiple correlation coefficient analysis, coefficient of determination analysis, as well as hypotheses using the t test and f test. The results of the regression equation are Y=15.156+0.647X1+0.743X2. The correlation coefficient value obtained was 0.877, meaning that the independent variable and the dependent variable had a very strong level of influence with a coefficient of determination or simultaneous influence of 79.0%, while the remaining 21.0% was influenced by variable not examined in the research.